CAKRAWALA HISTORIS PEMAHAMAN: WACANA HERMENEUTIKA HANS-GEORG GADAMER - Hendra Kaprisma (LITERASI: Indonesian Journal of Humanities, 2011)
This article discusses hermeneutics theory developed by Hans-Georg Gadamer (1900— 2002). Gadamer’s hermeneutics critically examines aesthetic crisis and historical understanding theory from a Heideggerian perspective. Hermeneutics is a classical discipline relating to textual understanding. Through Gadamer’s hermeneutic theory, interpreter understand the presented texts by relating them to their historical contexts. This way of understanding leads to a notion that interpreting texts not only means as reproducing meaning, but also as producing meaning beyon the texts.. In the text there is context. Therefore, interpreter should understand the historical horizon of textual and contextual understandings in order to establish its whole meaning. Keywords: hermeneutics, historicity, horizon, meaning